Ambientes de aprendizaje y su impacto en la autonomía de los niños de subnivel 2 de la Unidad Educativa Miguel Suárez Seminario de la ciudad de Puebloviejo - Zabala Campuzano, Roxana Patricia (2019)
The objective of the research carried out is to analyze the learning environments and their impact on the autonomy of children of sub-level 2 of the Miguel Suárez Seminar Educational Unit of the city of Puebloviejo, research that reflects a series of situations that are related to the interaction between educators and students in the educational learning process. The methodology implemented begins with the application of precise instruments to obtain relevant and relevant information on the topic raised, obtaining results that emphasize the relationship with the learning environment and the autonomy of children, because the basic characteristics such as safety and trust are recognized. to perform the activities in classes and meet the teacher's requirements